Deradicalization of Religion Models: Comparative Study of Jamaah Tablig Movement in The Region of Garut, Indonesia and Yala, Thailand - Hidayat, Asep Achmad; Januri, Fauzan; Syahid, Asep Ahmad; Samsudin, Samsudin (Historia Madania: Jurnal Ilmu Sejarah, 2018)
Deradicalization of religion will run on an ongoing basis when the power of the state is actively involved in it. That involvement can be shaped at the same time planning the implementation of policies, programs and budgets. In addition, the deradicalization of religion tends to be effective in the group of the owner of a basic understanding of religious inclusive. However, the practice of deradicalization of religion in Jama’ah Tabliq, which incidentally exclusive and fundamentalist, sustained even likely to be effective with minimal intervention of state power.Â This study aimed to describe the problem by uncovering and explaining the program that has been implemented Jama’ah Tabliq movement in deradicalization on those who embrace religious radicalism; The doctrine of Jama’ah Tabliq movement that managed to lose the attitude of the radicalism followers; and success factors Jama’ah Tabliq movement in conducting deradicalization. The approach in analyzing is the theoretical framework of power relations and the construction theory of history.Â With using qualitative methods and techniques as well as the locus descriptive analytical research and case studies Tablighi Jamaat movement in Garut, Indonesia, and Yala, Thailand, this research shows that,Â the first, deradicalization Tablighi Jama’a religious in the main program in the da’wah movement emphasizing the missionary movement of peace;Â the second,Â Â Jama’ah Tabliq doctrine, 1) the doctrine of ikromul Muslims, the honor and respect of every Muslim. 2) The doctrine or the doctrine of proselytizing and sermons. Jihad political set up and establish an Islamic State or seize political power of infidel countries is not mandatory, mandatory preached about the truth of Islam. 3) "four things that should not be done", namely the one discussed politics both inside and outside the country and discuss khilafiyah or differences of opinion in matters of religion; And third, the effectiveness and sustainability of the deradicalization of inter Jama’ah Tabliq are factors source of knowledge and practice everyday, the book "Fadhaiul Amal," which teaches the spirit and practice of peace.Â Â Referring to the book Jama’ah Tabliq develop the message to the model maqomi, intiqoli, ta’lim wata’lum, infirodi, non-political, and amaliyah dizkr.